Avoiding and Managing Error in Interventional Radiology Practice: Tips and Tools. Issue 4 (November 2020) - Mafeld, Sebastian; Musing, E. L. S.; Conway, Aaron; Kennedy, Sean; Oreopoulos, George; Rajan, Dheeraj
While there are limited data on error in interventional radiology (IR), the literature so far indicates that many errors in IR are potentially preventable. Yet, understanding the sources for error and implementing effective countermeasures can be challenging. Traditional methods for reducing error such as increased vigilance and new policies may be effective but can also contribute to an "error cycle." A hierarchy of effectiveness for patient safety interventions is outlined, and the characteristics of "high-reliability" organizations in other "high-risk" industries are examined for clues that could be implemented in IR. The evidence behind team error reduction strategies such as checklists is considered along with individual approaches such as "slowing down when you should." However, error in medicine is inevitable, and this article also seeks to outline an evidence-based approach to managing the psychological impact of being involved in medical error as a physician.